PENGUATAN LITERASI SAINS ANAK MELALUI AKTIVITAS STEM SEDERHANA DI TAMAN BACA MASYARAKAT KARYA MULYA - Esti Susiloningsih; Apit Fathurrohman; Suratmi Suratmi; Fahmi Surya Adikara; Ruri Tria Astika; Najlatul Fathia; Dwi Cahaya Nurani; Nabilah Mansur (LPPM Universitas Islam Darul 'Ulum Lamongan, 2026)
Strengthening science literacy in children is an important effort to develop critical thinking, creativity, and problem-solving skills from an early age. This Community Service aims to foster science literacy skills and strengthen children's science literacy through simple STEM activities at the Taman Baca Masyarakat Karya Mulya (TBM). The subjects consisted of 30 children and 10 volunteers participating in the regular activities at TBM. The implementation method involved STEM activities designed as simple experiments such as balloon rockets, mini windmills, and basic electricity experiments that integrate science, technology, engineering, and mathematics concepts. Data were collected through observation, documentation, and brief interviews. The results show that simple STEM activities can enhance curiosity, the inquiry process, and understanding of basic science concepts in children. In addition, collaborative activities in STEM projects also encourage children's communication skills and confidence in expressing their opinions. Thus, simple STEM activities at TBM Karya Mulya have proven effective as a strategy for strengthening children's science literacy in a non-formal learning environment.